Characterization of fetal microchimeric immune cells in mouse maternal hearts during physiologic and pathologic pregnancies - Lintao, Ryan C. V.; Kammala, Ananth Kumar; Radnaa, Enkhtuya; Bettayeb, Mohamed; Vincent, Kathleen L.; Patrikeev, Igor; Yaklic, Jerome; Bonney, Elizabeth A.; Menon, Ramkumar (Frontiers in Cell and Developmental Biology, 2023)
During pregnancy, fetal cells can be incorporated into maternal tissues (fetal microchimerism), where they can persist postpartum. Whether these fetal cells are beneficial or detrimental to maternal health is unknown. This study aimed to characterize fetal microchimeric immune cells in the maternal heart during pregnancy and postpartum, and to identify differences in these fetal microchimeric subpopulations between normal and pregnancies complicated by spontaneous preterm induced by ascending infection.A Cre reporter mouse model, which when mated with wild-type C57BL/6J females resulted in cells and tissues of progeny expressing red fluorescent protein tandem dimer Tomato (mT+), was used to detect fetal microchimeric cells. On embryonic day (E)15, 10 4 colony-forming units (CFU) E. coli was administered intravaginally to mimic ascending infection, with delivery on or before E18.5 considered as preterm delivery. A subset of pregnant mice was sacrificed at E16 and postpartum day 28 to harvest maternal hearts. Heart tissues were processed for immunofluorescence microscopy and high-dimensional mass cytometry by time-of-flight (CyTOF) using an antibody panel of immune cell markers. Changes in cardiac physiologic parameters were measured up to 60 days postpartum via two-dimensional echocardiography.Results: Intravaginal E. coli administration resulted in preterm delivery of live pups in 70% of the cases. mT+ expressing cells were detected in maternal uterus and heart, implying that fetal cells can migrate to different maternal compartments. During ascending infection, more fetal antigen-presenting cells (APCs) and less fetal hematopoietic stem cells (HSCs) and fetal double-positive (DP) thymocytes were observed in maternal hearts at E16 compared to normal pregnancy. These HSCs were cleared while DP thymocytes persisted 28 days postpartum following an ascending infection. No significant changes in cardiac physiologic parameters were observed postpartum except a trend in lowering the ejection fraction rate in preterm delivered mothers.: Both normal pregnancy and ascending infection revealed distinct compositions of fetal microchimeric immune cells within the maternal heart, which could potentially influence the maternal cardiac microenvironment via (1) modulation of cardiac reverse modeling processes by fetal stem cells, and (2) differential responses to recognition of fetal APCs by maternal T cells.